RELATIONSHIP BETWEEN UNDERSTANDING THE CONCEPT OF DIFFERENTIATED LEARNING AND TEACHERS' PEDAGOGICAL COMPETENCE IN SPECIAL SCHOOL KARANGANYAR - Regita Pramesti Agustika; Mahardika Supratiwi (Journal of Disability, 2025)
This study aims to determine the relationship between understanding the concept of differentiated learning and pedagogical competence of teachers in Special School Karanganyar. This study uses correlational quantitative research methods. The subjects of this study were 32 teachers at Special school Karanganyar. The data collection technique used the Understanding of Differentiated Learning Concepts Test (α = 0.856) and the Teacher Pedagogical Competence Scale (α = 0.913). Data analysis techniques using Pearson Product Moment. The results showed a correlation coefficient of 0.756 with a significance value of p = <0.001 or (rcount> rtable)) 0.756> 0.3388 and a significance value of p <0.05. It can be concluded that the hypothesis is accepted, namely that there is a significant relationship between understanding the concept of differentiated learning and the pedagogical competence of teachers in Special School Karanganyar. This strong positive relationship means that teachers' understanding of the concept of differentiated learning will increase along with their pedagogical competence. Thus it can be concluded that teachers' understanding of differentiated learning plays an important role and has a strong relationship with their pedagogical competence in Special School Karanganyar.